The Role Of Value In Halal Products Conscious Consumption: English - Salma Yunisa Vinanda Putri; Nila Armenia Windasari (International Journal of Emerging Issues in Islamic Studies, 2022)
Halal goods are a profitable market that is growing as a result of increasing birth rates and a growing young population and Muslims are expected to be outnumbered in the future. Sharia law requires that products used on a daily basis by Muslims include halal ingredients so they must understand what is permissible for them. The halal understanding factor is implemented at the level of consumption consciousness. This study aims to explore how people's conscious consumption behaviors are influenced by the perceived values associated with halal products. The researcher suggested a number of principles to be observed when converting to and using halal products. In this analysis, it is possible to predict people’s conscious consumption. Exploratory Factor Analysis was used to assess item validity and validity, and the actual data use multiple regression to ascertain the importance of a dependent variable, conscious use of halal goods, based on many factors as independent variables. Result shows only three values—safety concerns (SC), economic values (ECV), and environmental values (ENV)—that directly influence conscious consumption behavior (CCB) for halal products. Meanwhile religiosity positively moderates the social value (SOC) on conscious consumption behavior (CCB) for halal products.